2019
DOI: 10.21273/hortsci13704-18
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Responses of Two Herbaceous Peony Cultivars to Drought Stress

Abstract: Herbaceous peony is a perennial flowering plant with strong environmental adaptability and may be a good candidate for culture in arid areas. In this study, the physiological and biochemical responses of two herbaceous peony cultivars to different soil moisture gradients in pots were assessed by analyzing changes in 13 stress-related indices. The drought damage index (DDI) and the contents of malondialdehyde (MDA), soluble sugar, proline, and abscisic acid (ABA) generally increased as drought stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Alteration in APX activity in leaves is more common than in fibrous roots because APX mainly occurs in the chloroplast and cytoplasm and is a crucial enzyme for scavenging H 2 O 2 in chloroplasts [83]. Activities of SOD, POD, CAT and APX were altered and played a key role in protecting peony plants against acute water deficit [84]. The amount of non-enzymatic antioxidants (ascorbic acid, reduced glutathione and αtocopherol) and antioxidant enzymes (SOD, CAT and APX) activities were simultaneously enhanced in Coleus plectranthus in drought stress conditions [85].…”
Section: Drought Stress and Antioxidant Defense Systemmentioning
confidence: 99%
“…Alteration in APX activity in leaves is more common than in fibrous roots because APX mainly occurs in the chloroplast and cytoplasm and is a crucial enzyme for scavenging H 2 O 2 in chloroplasts [83]. Activities of SOD, POD, CAT and APX were altered and played a key role in protecting peony plants against acute water deficit [84]. The amount of non-enzymatic antioxidants (ascorbic acid, reduced glutathione and αtocopherol) and antioxidant enzymes (SOD, CAT and APX) activities were simultaneously enhanced in Coleus plectranthus in drought stress conditions [85].…”
Section: Drought Stress and Antioxidant Defense Systemmentioning
confidence: 99%
“…This finding agrees with those obtained by Dea, Brecht, Nunes, and Baldwin (2010), whereby the authors observed different firmness between the mangoes stored at 5°C and those stored at 12°C. As reported by Wang (1982) and Kays (1991), storage of fruits at chilling temperatures may lead to an increase in the rigidity of membrane resulting from the damage of membrane protein due to a decrease in micro-domains fluidity. However, no significant changes in TSS were observed between BS, control, and CI samples ( Figure 3C).…”
Section: Food Engineering Materials Science and Nanotechnologymentioning
confidence: 85%
“…In these regions, however, drought is a major stress factor affecting the cultivation of P. lactiflora . In P. lactiflora , the physiological and biochemical responses under drought stress were investigated [ 19 ], and drought stress changed the expression of differentially expressed genes (DEGs) involved in the reactive oxygen species (ROS) system, chlorophyll degradation and photosynthetic capacity, secondary pathways of biosynthesis, and sugar metabolism [ 20 ]. However, studies involving the TFs that regulate P. lactiflora DT are rarely reported.…”
Section: Introductionmentioning
confidence: 99%